ROLE OF WOMEN IN ENSURING ADEQUATE FOOD SECURITY IN iNDONESIA: lESSONS TO BE LEARNED - Kustantinah, Kustantinah (2011)
The projects are focused on role of woman in ensuring adequate food security through development of animal production by women's group applying the goat-sharing scheme. A total of 10 community projects have been set up by a university based livestock development project to enhance small ruminant production in rural comunities. As an example a women group was set up in 2007 in Gunungkidul district near Yogyakarta Jav a Indonesia. At the beginning of the project members of the group consisted of 30 women. Each were given 2 pregnant goats. The objectives of the scheme were to increased family income by improving goat population at the village and to increase motivation of farmer in goat management. A physical benefit to the members involved in the goat-sharing scheme is the ownerships of the kids. The number of kids kept by the participants depents on the number of kids born from the first two pregnancies. As the number of kids have to be shared with the community. After which the participants also owns the original female goats and all subsequent offspring. By 2011, the goat-sharing scheme had been running for over four years. The majority of the female goat allocated within the scheme were already in the third to fourth pregnancies. The other benefit of the goat-sharing scheme is production of manure, which is a very useful by products of goat keeping. The goat are kept in small pens beside their house and fed on by products from their fields as well as leaves from trees as a cut and carry system. It was rare for any of the member to sell goat faeces for cash beacause the manure has more value as fertilizer for crops. At this the total number of goats in the village are 410 heads, and the total members are 84. When the compost produced was applied to marginal land, much have being improved per year by utilization of the organic fertilizer. The programmes of animal production through goat-sharing scheme, are able to give rural women access to resources, and information, and enable them to the increase goat productivity, which benefit their families financial security.